A 6-bp deletion 5' to the G gamma globin gene in beta S chromosomes bearing the Bantu haplotype. - Bouhassira, E E (1990)
Sequencing of the upstream region of a human G gamma gene linked to the Bantu haplotype revealed a 6-bp deletion between site -400 and -395. Further analysis revealed that this mutation is present in 37% of the sickle cell anemia patients bearing the Bantu haplotype and is absent in the other haplotypes linked to the beta S gene, as well as in most chromosomes bearing the beta A-globin gene. The most parsimonious interpretation of the data is that the deletion is a very recent event which occurred in the subset of Bantu chromosomes already bearing a gene conversion of the A gamma gene by the G gamma gene. Its presence in black beta S chromosomes is most probably the consequence of a crossing-over between a Bantu beta S chromosome (with deletion and gene conversion) and a beta A chromosome.